Students’ and Teachers’ Perceptions of Diagnostic Tests in English Language Learning: A Case Study at Vocational High School 1 Limboto - Daud, Sintiya; Nurwati, Andi; Habibie , Alvons (ELITE JOURNAL, 2026)
This study explores students’ and teachers’ perceptions of diagnostic tests in English language learning at Vocational High School 1 Limboto, aiming to understand their roles, benefits, and implementation challenges within the Merdeka Curriculum context. Using a qualitative case study design, data were collected through in-depth interviews, classroom observations, and document analysis conducted between March–May 2025. Findings reveal that teachers routinely administer diagnostic tests at the beginning of each semester to map students’ initial abilities—particularly in grammar, vocabulary, and reading—and possess a strong conceptual understanding of diagnostic assessments as tools for identifying strengths and weaknesses, grouping learners, and designing differentiated instruction. Students perceive these tests as valuable reflective tools that enhance awareness of their learning needs and support focused skill development. Implementation is effective in preparation and administration stages but suboptimal in follow-up, as grouping and remedial actions remain informal. Supporting factors include teachers’ experience, clear planning, and positive classroom environments, while constraints involve limited time and institutional support. The study contributes to the literature by contextualizing diagnostic assessment in vocational education, highlighting the gap between understanding and practice, and emphasizing the need for systematic follow-up strategies to fully leverage assessment results in improving learning outcomes.